2019
DOI: 10.1111/ijpo.12567
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific association of plasma nesfatin‐1 concentrations with obesity in children

Abstract: Background: Nesfatin-1, an anorexigenic peptide, has been associated with food intake and thermogenesis, with discordant findings in humans and scarce studies in children to date.Objectives: The aim of this study was to analyze the relationship of obesity with nesfatin-1 levels in two cohorts of children.Methods: Plasma nesfatin-1 concentrations were analyzed in 6-to 9-year-olds (n = 140) and 12-to 16-year-old children (n = 96), including children with obesity and their sex-and age-matched normal-weight counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Regarding older children, five studies have explored serum nesfatin-1 levels in obese children (BMI > the 95th percentile) versus age- and sex-matched healthy children of normal weight. These results are conflicting, however [ 30 , 31 , 32 , 33 , 34 ]. One study reported significantly higher serum nesfatin-1 levels in obese children compared to normal-weight children [ 31 ] while the other studies reported significantly lower serum nesfatin-1 levels in obese children compared to normal-weight children (although one study only found this difference within girls) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding older children, five studies have explored serum nesfatin-1 levels in obese children (BMI > the 95th percentile) versus age- and sex-matched healthy children of normal weight. These results are conflicting, however [ 30 , 31 , 32 , 33 , 34 ]. One study reported significantly higher serum nesfatin-1 levels in obese children compared to normal-weight children [ 31 ] while the other studies reported significantly lower serum nesfatin-1 levels in obese children compared to normal-weight children (although one study only found this difference within girls) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are conflicting, however [ 30 , 31 , 32 , 33 , 34 ]. One study reported significantly higher serum nesfatin-1 levels in obese children compared to normal-weight children [ 31 ] while the other studies reported significantly lower serum nesfatin-1 levels in obese children compared to normal-weight children (although one study only found this difference within girls) [ 33 ]. A sixth study reported lower serum nesfatin-1 levels in healthy children who were underweight (defined as WAZ < 2 SD) and had poor appetite compared to healthy children with normal body weight [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated the relationship between nesfatin-1 levels and sex in children, but with different results. De Dios et al [29]indicated that nesfatin-1 concentrations were significantly lower in younger and older girls with obesity, while no significant differences were found in boys. In contrast, Kim et al [26] showed that nesfatin-1 levels were not significantly different between boys and girls; our finding fits well with the study of Kim et al, in which we found no significant difference in nesfatin-1 concentration between boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, nesfatin-1 is expressed in the central nervous system [7] , digestive system [8] , adipose tissue [9] , cardiovascular system [10] , etc. When it comes to the expression of nesfatin-1 in the reproductive system, mainly located in mouse OGCs, follicular membrane cells, endometrial epithelial cells and glands [11] , as well as testicular stromal cells [12] .…”
Section: Discussionmentioning
confidence: 99%